THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERINATOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Artificial intelligence (AI) plays a significant role in improving medical diagnostics, prognosis, and treatment processes in the field of perinatology. This article analyzes the applications, capabilities, and prospects of AI technologies in perinatal medicine. It also discusses how AI can enhance the effectiveness of perinatal care and addresses potential challenges associated with its use.